Slovarji in govorci - Stabej, Marko (Jezik in slovstvo, 2009)
As metalinguistic works dictionaries have three roles: symbolic, material and utilitarian. In the tradition of Slovene dictionary writing the latter is not the prevailing role, a fact that can be understood only on a cultural-historical and political-historical background. The consequence of this is that speakers do not have dictionaries available that would reliably help them with language-capability and communication difficulties, which weakens the prospects of the Slovene linguistics community.
Keywords: leksikografija; lexicography; slovarji; Slovene; slovenščina; sociolinguistics; sociolingvistika; zgodovina jezika; zgodovina slovenskega jezika